ARIAS Learning (Assurance, Relevance, Interest, Assesment and Satisfaction) in Social Studies - Purwanto, Devi Vitriana; Harmanto, Harmanto; Basuki, Ismet (Universitas Negeri Surabaya, 2019)
Assurance, Relevance, Interest, Assessment and Satisfaction (ARIAS) is one learning model to students center. This learning model emphasizes the delivery the activeness of students in the class. In the implementation of this model has the five components which consists of five integrated components needed in the learning activities (1) assurance which foster student?s self-confidence, (2) relevance which connect the material with student?s real life, (3) interest which grow the student?s interest, (4) assessment which is an student assessment, and (5) satisfaction which provide a sense of proud to student. The aim of this research was to describe the teacher's ability to manage learning, student activities, student learning, and students' response using ARIAS learning model. Research conducted on the use of the model of ARIAS in social studies so far shown significant result on increase students? understanding of social studies consepts. The Application Assurance, Relevance, Interest, Assessment and Satisfaction (ARIAS) learning model can increase student learning outcomes social studies.